Sketsa Dakwah Islam di Eropa Barat - Aliyudin, Aliyudin (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung, 2008)
The history of DakwahÂ in West-EropaÂ can be devided in two patterns: The first, from century 8th to 15th , named at least as politic dakwah. Muslims have real authority in some areas: a few islands in midle sea and minor place in south-Italia and Franch, nor Spanish and Sicilia. The second, sine 19th centuryÂ till now, muslims havenât political authority. The pattern of dakwah only depend on profile, personality, performance of muslim imigransÂ behavior as worker, trader, student, diplomat, ect.